Forearm Fractures in Children: Split Opinions about Splitting the Cast - Schulte, Daniel; Habernig, Sandra; Zuzak, Tycho; Staubli, Georg; Altermatt, Stefan; Horst, Maya; Garcia, Daniel (European Journal of Pediatric Surgery, 2014)
Background Fractures of the forearm are the most common fractures in children. Various methods of cast immobilization have been recommended. Currently, there is still controversy regarding the optimal method of treatment, especially regarding the need for cast splitting.Methods We conducted a single-center randomized and controlled trial between June 2008 and September 2009. Children younger than 16 years presenting to the emergency department with a closed fracture of the forearm needing reduction were eligible for random assignment to immobilization in a closed or split circumferential semirigid cast. The primary outcome was the incidence of cast-related soft-tissue problems such as compartment syndrome, neurovascular compromise, saw burns, or skin breakdown. The secondary outcome was fracture stability.Results During this period, 100 patients were randomly assigned to one of the two procedures and analyzed. Follow-up was completed in 99 patients. No compartment syndrome was observed in either group. Moderate skin breakdown (< 2 cm2) occurred in two patients, one in the closed cast and one in the split cast group. Secondary splitting was necessary in one patient because of a reversible lymphedema. Significant secondary displacement of the fracture was slightly more common in the split group (5 of 50 patients [10%] vs. 4 of 49 patients [8%] in the closed cast group) without reaching statistical significance.Conclusions No significant difference in the incidence of cast-related problems was observed between the groups. Fracture stability was comparable in both groups. We suggest that closed circumferential semirigid casts are a safe and effective immobilization technique for fractures of the forearm in children and splitting can be omitted.
Keywords: forearm fractures in children; closed versus split cast; soft-tissue problems; fracture stability